2017
DOI: 10.1002/2017jd026803
|View full text |Cite
|
Sign up to set email alerts
|

The impact of air pollutants on rainwater chemistry during “urban‐induced heavy rainfall” in downtown Tokyo, Japan

Abstract: In order to clarify the impact of air pollution on the formation of sudden and locally distributed heavy rain in urban areas (hereafter UHR = urban‐induced heavy rain), we analyzed inorganic ions in rainwater samples collected on an event basis over 5 years from October 2012 to December 2016 in Shinjuku, Tokyo. Hourly rainfall amounts and wet deposition fluxes of acidic components (the sum of H+, NH4+, NO3−, and nonsea‐salt SO42−) in UHR were 13.1 and 17.8 times larger than those in normal rainfall, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Nitrogen oxides combines with water vapor in the atmosphere to form acids which when precipitation takes place, it led to lower pH as seen from the Table 1 with high concentration of NO 3 À ,NO 2 À and NH 4 + respectively. Due to presence of aerosols from interactions with water vapor and other particulates, there is potential for nitrogen groups to combine forming (NH 4 )HSO 4 , (NH 4 ) 2 SO 4 ,NH 4 NO 3 and NH 4 NO 2 that can dissolve into cloud droplets forming smog with sulfate groups which has adverse effects on health issues such as asthma attack, difficulty to breath well [48]. According to Ohara, [49], presence of free radicals or reactive ions of anionic oxide can react with ozone causing decrease in ozone content by influence of ultraviolet radiation from the sun.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen oxides combines with water vapor in the atmosphere to form acids which when precipitation takes place, it led to lower pH as seen from the Table 1 with high concentration of NO 3 À ,NO 2 À and NH 4 + respectively. Due to presence of aerosols from interactions with water vapor and other particulates, there is potential for nitrogen groups to combine forming (NH 4 )HSO 4 , (NH 4 ) 2 SO 4 ,NH 4 NO 3 and NH 4 NO 2 that can dissolve into cloud droplets forming smog with sulfate groups which has adverse effects on health issues such as asthma attack, difficulty to breath well [48]. According to Ohara, [49], presence of free radicals or reactive ions of anionic oxide can react with ozone causing decrease in ozone content by influence of ultraviolet radiation from the sun.…”
Section: Discussionmentioning
confidence: 99%
“…This is because washout (below cloud scavenging) is a major mechanism by which atmospheric contaminants are incorporated in rainfall. 5,60,61 The composition of rain reflects that of the atmosphere through which it falls and consists of a mixture of natural (e.g., soil dust) and anthropogenic (e.g., industrial and vehicular emissions) chemicals. 62,63 Metals of dominantly crustal origin (Fe, Al) constitute the largest fraction of the total metal content in rain, accounting for >75% of the analyzed metals.…”
Section: Elemental Concentrationsmentioning
confidence: 99%
“…2,3 Rain washes gaseous, organic, inorganic, and particulate pollutants released into the atmosphere and deposited on impervious surfaces into surface waterbodies. [4][5][6] The volume of urban runoff generated annually in the United States is equivalent to the volume of treated wastewater and is estimated at 38 112 billion liters. 7 Unlike sewage and wastewater, in most cases urban runoff enters public waters without any treatment resulting in a direct discharge of pollutants to receiving waterbodies.…”
Section: Introductionmentioning
confidence: 99%
“…So, the precipitation has increased with decrease in temperature and the finding is in line with research done by Patni and Jindal, [18] in which they have analyzed the rainfall intensity has increased in summers from March to May 2020 in between COVID-19 pandemic lockdown. Also, the observations related to rainfall in lockdown period are very fluctuating and the impact of air pollution on rainfall pattern is very uncertain but we can consider the reduced emissions as a major cause of erratic rainfall pattern in the region under lockdown Uchiyama et al, [19]; American Association For The Advancement of Science news, [20]. Also, in another research by Bhat et al [21] has revealed that unpredicted rainfall patterns have increased as a result of indirect impact of COVID-19 lockdown in Jammu & Kashmir.…”
Section: Variation In Rainfallmentioning
confidence: 99%